The usage of artificial intelligence in marketing automation: potentials and pitfalls / Wan Fariza Wan Abdul Rahman ...[et al.] - Wan Abdul Rahman, Wan Fariza; Che Fauzi, Ainul Azila; Wan Husain, Wan Salfarina; Che Hassan, Siti Hasrinafasya; Nik Kamaruzaman, Nik Nahdiya; Wan Aziz, Wan Adibah Hanis (Unit Penerbitan UiTM Kelantan, 2020)
Abstract: Marketing automation, neuro marketing, and users' personalization have been booming with the rise of Internet revolution and digital marketing. Due to the accumulation of rich consumer data generated from social engines, the AI-based marketing application is now taking a wide leap. This article attempts to address the prominent use of Artificial Intelligence (AI) in marketing in term of its potentials in becoming a pervasive part of today's competitive world. The basic concept of AI is presented so that thorough understanding on its application in marketing can be grasped. Dealing with the dynamic nature of marketing and people's sensitive data, despite of the opportunies offered, the pitfalls of AI in marketing automation should be taken into consideration. The security issues concerning the users' privacy and possible malicious activities are highlighted in this article.